PENGARUH PEMBERIAN MINUMAN MADU KUNYIT TERHADAP TINGKAT NYERI MENSTRUASI - Retno Widowati; Rini Kundaryanti; Novi Ernawati (Universitas Nasional, 2020)
The research aimed to determine the effect of honey turmeric drinks to the level of menstrual pain (dysmenorrhea). The research design was quasi-experiment with one-group pretest-posttest. The research sample consisted of 17 respondents consisting students of Midwifery Study Program, Universitas Nasional. The sampling technique used purposive sampling. Data were analyzed using descriptive statistics and non-parametric statistical tests using the Wilcoxon Test with the significance level of A.sympSig (2-tailed) <α = 0.05. Honey turmeric drink was given 3 times a day as much as 150 mL for 2 days. Pain intensity was measured using Numeric Rating Scale (NRS) before and after administration of honey turmeric drink. The length of time between pretest and posttest was according to the respondent's menstrual cycle. Statistical test results showed the value of NRS before and after drink the honey turmeric 3.12 and 1.94. The test results obtained significant difference Asymp Sig (two-tailed) = 0,000. The research showed there was a significant difference of honey turmeric drink on the level of menstrual pain, as well as reducing the scale of menstrual pain.